Geodesia as a support tool for the pantanal neotectonics understanding: The corumbá fluviometric station example, mato grosso do sul, Brazil - Paranhos Filho, Antônio Conceição; Amorim, Gustavo Marques E.; Machado, Rômulo; Marcato, José; Prol, Fabricio Dos Santos [UNESP]; Oliveira, Jose Renato Silva de; Mioto, Camila Leonardo (Universidade Federal do Rio de Janeiro, 2018)
Global Navigation Satellite Systems (GNSS) were initially designed to extend the coverage and accuracy of navigation systems, but given the possible applications, it is possible to analyze the different terrestrial phenomena from a specific methodology. how to estimate the speed and direction of the plate tectonics or blocks where the stations rest. In the present work we sought to extend and derive GNSS applications, seeking to better understand the regional geotectonics of the Pantanal Sedimentary Basin. In this sense, the combination of SIRGAS (Geocentric Reference System for the Americas) GNSS speed data with water surface data in times of flood and drought was modeled. From the obtained results, it can be concluded that the variation in the volume and weight of the water during the times of flood and of drought are reflected in the position of the height ruler located in Corumbá-MS. This volume of water, in addition to promoting the reactivation of tectonic structures, exerts a lubricating effect on regional faults and fractures, and may act as a facilitator or inducer of regional earthquakes.
Geodésia como ferramenta de apoio a compreensão da neotectônica do pantanal: Exemplo na estação fluviométrica de corumbá, mato grosso do sul, Brasil
Keywords: GNSS; Seismicity; Tectonics